1999
DOI: 10.1042/0264-6021:3440643
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro manipulation of carbohydrate metabolism: a new strategy for deciphering the cellular defence mechanisms against nitric oxide attack

Abstract: This study was aimed at examining the effects of manipulating the carbohydrate source of the culture medium on the cellular sensitivity of epithelial cells to an oxidative attack. Our rationale was that substituting galactose for glucose in culture media would remove the protection afforded by glucose utilization in two major metabolic pathways, i.e. anaerobic glycolysis and\or the pentose phosphate pathway (PPP), which builds up cellular reducing power. Indeed, we show that the polarized human colonic epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 36 publications
6
41
0
Order By: Relevance
“…30 We now extend these findings to show that Bcl-x L is protective even when glycolysis is blocked by 2-DG. It is possible that 2-DG-6-phosphate produced by HK-mediated phosphorylation of 2-DG can enter the pentose phosphate shunt and allow NADPH recycling, 49 thereby maintaining a reduced cellular state and contributing towards cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…30 We now extend these findings to show that Bcl-x L is protective even when glycolysis is blocked by 2-DG. It is possible that 2-DG-6-phosphate produced by HK-mediated phosphorylation of 2-DG can enter the pentose phosphate shunt and allow NADPH recycling, 49 thereby maintaining a reduced cellular state and contributing towards cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…However, this needs to be directly verified using a catalytically inactive mutant of hexokinase. Other investigators have demonstrated that 2-deoxyglucose-6-phosphate, generated via the action of hexokinase, can be metabolized via the pentose phosphate pathway (PPP) in quantities sufficient to support redox coupling critical for cell survival (Le Goffe et al, 1999Goffe et al, , 2002 and redox coupling between this pathway and caspase-2 activation has also recently been described (Nutt et al, 2005), so potential metabolic contributions distal to glucose phosphorylation cannot be excluded (see below).…”
Section: Mitochondrial Hexokinases As Downstream Effectors Of Growth mentioning
confidence: 99%
“…The generation of glucose-6-phosphate is required for entry into the PPP (Figure 1). Thus, glucose phosphorylation by hexokinase could gate flux through this pathway and thereby directly contribute to both cellular redox status and resistance to oxidant-mediated cell death (Le Goffe et al, 1999Tian et al, 1999;Kurata et al, 2000). Glucose-6-phosphate dehydrogenase (G6PDH) activity is rate-limiting for PPP flux and is required for NADPH generation via this route.…”
Section: How Do Growth Factors and Akt Mediate Hexokinase-mitochondrimentioning
confidence: 99%
“…The concentration of ni- trated proteins was estimated from the standard curve and expressed as micrograms of nitro-BSA equivalent per milligram of protein. 22 Cytochrome C Determination. Cytochrome c concentrations were determined on cytosolic fractions or on enriched mitochondrial fractions from livers of treated or untreated ob/ob mice.…”
Section: Methodsmentioning
confidence: 99%